2022
DOI: 10.1080/21645515.2022.2031776
|View full text |Cite
|
Sign up to set email alerts
|

Evolving measles status and immunization policy development in six European countries

Abstract: Developing and implementing new immunization policies in response to shifting epidemiology is a critical public health component. We adopted a mixed-methods approach (via narrative literature review [101 articles] and 9 semi-structured interviews) to evaluate policy development in response to shifting measles epidemiology in six European countries (Italy, Belgium, Germany, Romania, UK, and Ukraine); where policies and strategies have evolved in response to country-specific disease and vaccination patterns. Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 125 publications
0
9
0
1
Order By: Relevance
“…After duplicates were removed, the titles and abstracts of 1,628 reports were reviewed by one of the authors (JFL), and 131 met the eligibility criteria (Figure 1). The current review was primarily based on 107 full papers, 2‐108 but, due to the scarcity of data, we also chose to cite five relevant abstracts 109‐113 for a more complete picture of child health in Ukraine. Our literature search was limited to papers published in English.…”
Section: Methodsmentioning
confidence: 99%
“…After duplicates were removed, the titles and abstracts of 1,628 reports were reviewed by one of the authors (JFL), and 131 met the eligibility criteria (Figure 1). The current review was primarily based on 107 full papers, 2‐108 but, due to the scarcity of data, we also chose to cite five relevant abstracts 109‐113 for a more complete picture of child health in Ukraine. Our literature search was limited to papers published in English.…”
Section: Methodsmentioning
confidence: 99%
“…hätte vorbeugen können. Der gelegentlich, auch von irregeleitetem medizinischen Fachpersonal, vertretenen Auffassung, dass Masern eine leichte Erkrankung und das Überstehen der Erkrankung für die Entwicklung des Kindes förderlich seien, gilt es entgegenzutreten [ 5 ]. Falls die Eltern der stationären Aufnahme zustimmen, ist später Zeit, über die ausstehenden Impfungen zu diskutieren und ggf.…”
Section: Prüfungsfragenunclassified
“…Over 20 years ago, Wakefield [ 9 ] published a later retracted and disproven paper claiming that childhood vaccinations lead to autism. This claim has driven parental hesitancy regarding child vaccinations and contributed to a resurgence in preventable childhood diseases [ 10 ]. A systematic review by Borges Do Nascimento and colleagues [ 11 ] found that misinformation can create more disharmony among people, lead to delays in obtaining healthcare, and contribute to misinterpretations of evidence.…”
Section: Introductionmentioning
confidence: 99%